2008
DOI: 10.1063/1.2940736
|View full text |Cite
|
Sign up to set email alerts
|

Increase in oxide hole trap density associated with nitrogen incorporation at the SiO2/SiC interface

Abstract: Nitrogen incorporation at the SiO2/SiC interface via high temperature nitric oxide annealing leads to the passivation of electrically active interface defects, yielding improved inversion mobility in the semiconductor. However, we find that such nitrided oxides can possess a larger density of hole traps than as-grown oxides, which is detrimental to the reliability of devices (e.g., can lead to large threshold voltage instabilities and to accelerated failure). Three different charge injection techniques are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 35 publications
4
39
1
Order By: Relevance
“…Adapted from Refs. [103,104] region of the oxide. Since we have shown that more nitrogen would increase the mobility even further, other nitridation methods could maximize its density while confining it to the interface boundary.…”
Section: No Annealingmentioning
confidence: 99%
See 2 more Smart Citations
“…Adapted from Refs. [103,104] region of the oxide. Since we have shown that more nitrogen would increase the mobility even further, other nitridation methods could maximize its density while confining it to the interface boundary.…”
Section: No Annealingmentioning
confidence: 99%
“…This can be of concern even for n-channel transistors to which a negative gate bias can be applied to ensure that it is OFF in its idle state. Several methods have been used to accelerate hole exposure of the gate oxide such as x-ray irradiation [52], Fowler-Nordheim tunneling, and internal photoemission [104]. Figs.…”
Section: No Annealingmentioning
confidence: 99%
See 1 more Smart Citation
“…1 from TSC curves measured at V rev = À100 V were N t,1 = 2. 25 ). The three TSC peak groups varied differently with bias.…”
Section: Tsc Spectra Of Mosfet Source/body N + -P Junctionmentioning
confidence: 99%
“…24 Rozen et al have attributed the higher density of hole traps in NO-annealed oxides to the increased nitrogen incorporation at sites near the interface. 25 …”
mentioning
confidence: 99%